2003
DOI: 10.1021/bp034075t
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of 3′‐Hydroxyacetaminophen Catalyzed by Tyrosinase

Abstract: 3'-Hydroxyacetaminophen, a catechol metabolite of N-acetyl-p-aminophenol (acetaminophen) and N-acetyl-m-aminophenol (a structural analogue of acetaminophen and considered as a possible alternative because it is not hepatotoxic), is enzymatically synthesized for the first time using mushroom tyrosinase. Although reported to be weakly hepatotoxic in vivo, this catechol derivative of acetaminophen is not commercially available. This compound was obtained from its monophenolic precursor, acetaminophen, using the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…The attainment of the o-diphenol is in agreement with the general behavior of tyrosinase when acting on monophenols under reducing conditions (Valero et al, 2003). To evaluate the possibility that dopaxanthin was a substrate of the diphenolase activity of the enzyme, a solution of the pigment was prepared in phosphate buffer, pH 6.0, and tyrosinase was added.…”
Section: Extraction and Purification Of Dopaxanthin From Yellow Flowesupporting
confidence: 67%
“…The attainment of the o-diphenol is in agreement with the general behavior of tyrosinase when acting on monophenols under reducing conditions (Valero et al, 2003). To evaluate the possibility that dopaxanthin was a substrate of the diphenolase activity of the enzyme, a solution of the pigment was prepared in phosphate buffer, pH 6.0, and tyrosinase was added.…”
Section: Extraction and Purification Of Dopaxanthin From Yellow Flowesupporting
confidence: 67%
“…The peak derived from the activity of tyrosinase was assigned to dopaminebetaxanthin by co-elution and comparison of spectral properties with dopamine-betaxanthin directly synthesized from betalamic acid. The o-diphenol obtained is in agreement with the general behavior of tyrosinase when acting on monophenols under reducing conditions (Valero et al 2003) and indicates that the quinone was formed, although it could not be detected in the absence of AA.…”
Section: Enzymatic Conversion Of Tyramine-betaxanthin To Dopamine-betsupporting
confidence: 81%
“…Previously, we reported that similar to levodopa, the potency of α-methyldopa, a catecholic oral drug, was rapidly diminished by enzymes present in bananas [ 3 ]. Meanwhile, mushroom-derived tyrosinase was determined to catalyze the catecholation reaction by the oxidation of acetaminophen [ 8 , 9 ]. In our study, loss of acetaminophen potency in the presence of bananas may be due to the abundance of polyphenol oxidase, which normally catalyzes the conversion of tyrosine ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ions derived from the metabolite were confirmed on the LC/ESI/MS spectrum ( Fig 7 ). The oxidation reaction catalyzed by 3-hydroxyacetaminofen tyrosinase activity is reported to be reversibly inhibited by ascorbic acid [ 8 ]. Conversely, to prove that the tyrosinase in bananas causes the interaction, we must show that PPO from bananas converts acetaminophen into APAP oxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation